1873 Neb. Laws 724, ch. 58, § 25 - (:unkn) unknown (General Publisher, 1873)
Prohibited the conceal carry of a pistol, Bowie-knife, dirk, or any other dangerous weapon. First offense punished with a fine not exceeding two hundred dollars or imprisoned for not more than thirty days. Second offense fined not exceeding five hundred dollars, or jailed not exceeding three months, or both.
--
Keywords: CARRY - CONCEALED